GLOBALIZATION AND INTEGRATION IN THE ECONOMY OF NETWORKS: https://doi.org/10.5281/zenodo.14738753 - Sunnatov , Qudratulla (International scientific and practical conference, 2025)
This article analyzes the impact of globalization processes on integration in the network economy. Globalization strengthens the interconnection and cooperation in various sectors of economic activity, which plays a significant role in the effective allocation of resources and technologies, the creation of new business opportunities, and ensuring economic growth. Integration in the network economy, in turn, supports the development of trade, investment, technological exchange, labor market integration, and the growth of new economic structures. The article discusses the economic, social, and ecological impacts of globalization as well as the new opportunities emerging in the network economy due to integration processes.